Geese, economic practices and religion in northern Roman Gaul. (April 2023) - Bourgois, Alice; Duval, Colin
Highlights: This paper offers a holistic approach of the relationship between geese and men in northern Roman Gaul, with an opening to the whole Roman world. The article contains many new and unpublished zooarchaeological data from recent excavations driven in Meaux, Vendeuil-Caply and the Paris region. The goose played a major role in the diet and economy of the city of Meaux, this case appear to be unique in the Roman world. At Vendeuil-Caply, goose and chicken bones were associated with more than 200 fragments of goddesses statuettes and bird figurines. The article highlights the possible link between goose breeding and consumption and the cult of certain ancient goddesses. Abstract: The proportion of geese ( Anser sp .) in the zooarchaeological samples from northern Gaul increased considerably from the Roman period onwards, though the development of their husbandry and the methods of their exploitation remain largely unknown. However, the recent production of regional syntheses and the discovery of sites particularly rich in goose remains now make it possible to address questions concerning the role of this bird within Gallic culture and economy during antiquity. The data reveal that geese, unlike chickens ( Gallus gallus domesticus ), were unevenly spread – the species was well established in certain towns and sanctuaries in the Paris region and Picardy, but was very discreet elsewhere. This geographical heterogeneity and the probable link between the goose and certain places of worship suggest that its breeding and consumption may have been dependent on particular social, cultural and religious influences. More so than other animals, the goose may reflect the social status and religious obedience of the populations that kept and consumed it.